Simulation modelling and analysis of crowd evacuation by utilizing evolutionary stable strategy - Mohd Ibrahim, Azhar; Venkat, Ibrahim; Khader, Ahamad Tajudin (ICIC International, 2016)
Crowd and evacuation management has been active areas of research and study in the recent past. Various developments continue to take place in the process of efficient evacuation of crowd in mass gatherings. This article is intended to provide an analysis on crowd evacuation models based on the game theory approach. There will be interaction among evacuees in which the evacuees tend to be either cooperator or defector in order to move towards desired path. This paper analyzes in detail the pure and mixed strategy of Nash Equilibrium (NE) and Evolutionary Stable Strategy (ESS) as a result of different types of interaction among evacuees under different scenarios that possibly could happen during normal and emergency evacuation. We found out that due to the higher cost of interrupting than the value of benefit able to move, the proportion of defectors playing the ESS will decrease compared to the proportion of cooperators playing the ESS.